2006
DOI: 10.1136/bmj.38849.440914.ae
|View full text |Cite
|
Sign up to set email alerts
|

Impact of specialty of admitting physician and type of hospital on care and outcome for myocardial infarction in England and Wales during 2004-5: observational study

Abstract: Objective To examine process of care and outcome for patients admitted with acute myocardial infarction to hospitals in England and Wales in relation to type of consultant care and type of hospital. Design Observational study of 88 782 patients admitted with myocardial infarction during 2004-5, using records from the national audit of myocardial infarction project (MINAP) database. Outcome measures Use of reperfusion treatment and secondary prevention drugs, use of angiography, and 90 day mortality of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 20 publications
4
52
1
1
Order By: Relevance
“…10 The percentage of use in these 3 studies ranged from 57%-81% for ACE inhibitors, 71%-79% for beta-blockers, and 35%-91% for statins. [10][11][12] Our reported use rates are lower than these ranges except for the Austin et al study that showed an extremely low rate of statin use (36%) after hospital discharge (from April 1, 1999, through March 31, 2001). 10 Our lower exposure rates may be explained partly by a difference in methodology.…”
Section: ■■ Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…10 The percentage of use in these 3 studies ranged from 57%-81% for ACE inhibitors, 71%-79% for beta-blockers, and 35%-91% for statins. [10][11][12] Our reported use rates are lower than these ranges except for the Austin et al study that showed an extremely low rate of statin use (36%) after hospital discharge (from April 1, 1999, through March 31, 2001). 10 Our lower exposure rates may be explained partly by a difference in methodology.…”
Section: ■■ Discussioncontrasting
confidence: 43%
“…There were 14.2% to 26% fewer patients using ACE inhibitors, beta-blockers, or statins in the age category ≥ 85 years compared with the younger group aged 55-64 years. 12 Austin et al reported that patients who were not prescribed a statin after acute MI were older (mean age 70 years for those who were not prescribed a statin compared with 64 years for those prescribed a statin, P < 0.001), and a higher percent was female (40% of those not prescribed a statin and 29% of those prescribed a statin were women, P < 0.001). 10 Doyle et al analyzed gender differences in 1,356 hospitalized cardiac ACS patients and noted far fewer women in the study, 28%, compared with men, 72%; and the average age was 6 years higher for women (69 years) than for men (63 years, P < 0.001).…”
Section: Use Of Secondary Prevention Drug Therapy In Patients With Acmentioning
confidence: 99%
“…A recent report has clearly demonstrated that in English and Welsh hospitals, most patients who had AMI and were admitted under the care of non-cardiologists had a substantially higher all cause mortality. 8 This report clearly demonstrated that AMI patients cared for by cardiologists were more likely to receive proven treatments and angiography and had less co-morbidity than other patients. 8 As clinical biochemists, it should be our role to encourage the utilization of evidence-based practice, to increase appropriate test usage, mitigate misuse and recommend referral if deemed necessary.…”
Section: Discussionmentioning
confidence: 85%
“…8 Outcomes are improved when acute cardiac care is delivered by cardiologists on a cardiology ward. [8][9][10] therefore all hospitals should have access to an Acute Cardiac Care Unit with appropriate staffing, if they are admitting patients with medical condition like in the acute phase of their ischemic syndrome, pulmonary edema ,heart failure, cardiac shock, arrhythmia or other hemodynamic disturbance. 9 In clinical practice irrational prescription of drugs is a common occurrence.…”
Section: Introductionmentioning
confidence: 99%